Peran Undang-Undang Perlindungan Data Pribadi dan Hukum Telekomunikasi dalam SPBE di Indonesia - Three Boy; Ariawan Ariawan (UNES Law Review, 2023)
Digital transformation is an inevitability that covers all aspects of human life with the use of Information and Communication Technology (ICT). In the era of digital transformation, implementing SPBE in Indonesia is very important to increase government accountability and the effectiveness of public services. The research was conducted using qualitative methods, which focused on using secondary sources of information from literature to investigate the material further. Currently there is a Law on Personal Data Protection, namely "Law Number 27 of 2022 concerning Personal Data Protection", where the existence of this Law is very important because it can become a strong legal basis and guarantee that the State ensures the protection of personal data, especially from cyber crime. In general, telecommunications law includes a set of rules and regulations governing the use of communications technology, including the sending and receiving of information over electronic networks. Telecommunications law as well as the Personal Data Protection Law must provide a legal basis for handling cyber security incidents, including reporting procedures, investigations and law enforcement against cybercriminals.